Detection of Lysteria monocytogenes in Frozen Meatballs Using Real-Time PCR - Sophian, Alfi; Purwaningsih, Ratna (Department of Technology of Agricultural product (THP) Jambi University, 2022)
Detection of pathogenic bacteria Listeria monocytogenes in processed food products of frozen meatballs is one of the critical test parameters in product quality testing. The challenge in testing product quality is how to find a reliable and effective test method to generate test results data. With this research, it is hoped that it can provide information or references for similar research. The method used in this research is the enrichment method with a direct isolation technique and amplification using real-time PCR. Data analysis was carried out based on 2 main criteria which included: (1) Ct analysis (Cycle threshold) and (2) melting temperature (Tm) analysis. From the results of the analysis using real-time PCR, the results of the tested samples were detected at Ct 11.60 with a Tm value of 81.50. For NTC control not detected, this indicates that the master mix used is in good condition and no contamination occurred when testing the sample. The use of this NTC control plays an important role in monitoring the quality of the master mic and test run. For the LOD control and positive control, the results were detected, whereas in the LOD control, the Ct value was detected at 10.08 and the Tm value was at 81.30. for positive control, the value of Ct was detected at 10.85 and the value of Tm was at 82.0. Based on the results of the study, it can be concluded that the test method used can detect Listeria monocytogenes in processed meat products in the form of frozen meatballs.